Using the Direct Method for Learning Maharah Kalam in Sidoarjo Regency: Penggunaan Metode Langsung untuk Pembelajaran Maharah Kalam di Kabupaten Sidoarjo - Nuzula, Firdausin; Fauji, Imam (Universitas Muhammadiyah Sidoarjo, 2022)
This article aims to determine the process of using the Direct Method for learning Maharah Kalam at Ma'had Umar bin Khattab Sidoarjo, in the Tamhidi class. This study uses a qualitative descriptive approach in which the data are in the form of words or sentences obtained from informants or research subjects. The results showed that the use of the direct method for learning Maharah Kalam at Ma'had Umar bin Khattab Sidoarjo, in the Tamhidi class was still in the business stage, so the learning process had not fully used Arabic.